2019
DOI: 10.1017/dmp.2019.112
|View full text |Cite
|
Sign up to set email alerts
|

Emergency and Disaster Preparedness of European Hospital Pharmacists: A Survey

Abstract: Objective: This study was focused on reviewing the emergency and disaster preparedness of European hospital pharmacists. Methods: An online survey based on International Pharmaceutical Federation (FIP) guidelines for natural disasters was sent to European hospital pharmacies, with the support of the European Association of Hospital Pharmacists. Additional questions were added about the characteristics of respondents, as well as preparedness and experience of manmade disasters. Descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…As illustrated by the stress-test of healthcare system that COVID-19 pandemic conducted recently, many European countries are not well-prepared to maintain the continuity of long-term therapies in unfavourable conditions [ ( Kardas et al, 2021 )]. This is also a case of pharmaceutical service: a recent survey has shown that European hospital pharmacies are rather poorly prepared to emergencies and disasters ( Schumacher et al, 2021 ). Fortunately, a crisis preparedness can be improved due to dedicated training ( Schumacher et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated by the stress-test of healthcare system that COVID-19 pandemic conducted recently, many European countries are not well-prepared to maintain the continuity of long-term therapies in unfavourable conditions [ ( Kardas et al, 2021 )]. This is also a case of pharmaceutical service: a recent survey has shown that European hospital pharmacies are rather poorly prepared to emergencies and disasters ( Schumacher et al, 2021 ). Fortunately, a crisis preparedness can be improved due to dedicated training ( Schumacher et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted with participants from 27 countries in Europe, 15% had a disaster response experience on the job. While 56% of the participants who had disaster response experience, were knowledgeable about the procedure to be performed in case of a disaster, this rate was 23% in those who did not have disaster response experience (28). In a study conducted to investigate a postdisaster situation in Taiwan, healthcare professionals stated that the hospital they worked in was inadequate in terms of disaster preparedness and that they had difficulties in maintaining services (29).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of community pharmacists regarding disaster medicine preparedness and readiness is extremely important. Several studies about disaster medicine preparedness and readiness among health care workers [33][34][35][36]. However, there was no previous study about this issue among community pharmacists in the UAE.…”
Section: Plos Onementioning
confidence: 99%